Marketing to Senior Consumers (West and India): A Review - Sharma, Adya (Indian Journal of Marketing, 2010)
The Marketing world, has in general, tended to focus their attention on younger consumers with less attention given to those over fifty. However, the world is undergoing a demographic transition. The 60+ group formed 5% of the population in the year 1970, but would form 16% of the population by 2050. This demographic segment is growing at about 2% every year, 60% faster than the total population (Population division of department of economic and social affairs of UN secretariat, 2004). Global Action on ageing advocates at the United Nations in New York to build a better society for older people across the globe. Numbers of older persons are increasing rapidly. One out of every 10 persons is now 60 years or above. By 2050, one out of five will be 60 years or older (Globalaging.org). This segment is definitely valuable because with increase in education etc., their financial worth has increased, they do have purchasing power. UN member states correctly see this growth among the elderly as a tremendous economic and social challenge for their countries and the world (globalaging.org). Marketers cannot ignore this segment any more. With the changes in population distribution, society and family structures and health treatment methods and technologies, the senior citizens in the future will have higher education levels, better health and more personal wealth. These future senior citizens thus, will demand higher standards for their independent life qualities (Yao-Tsung Tsai, 2006). A study shows that in general, senior citizens are participating in more activities than they were ten years ago which may be due to more resources (Agahi and Parker, 2005). Across Asia, an age shift is taking place. If the current trend continues, then by mid century, the percentage of older consumers will double or triple in East Asia. In the past, being old too often meant being infirm but thanks to better health care, better nutrition and better housing, people in their third age are much more active and demanding (asiafoodjournal.com). India has emerged as an attractive market for many reasons, one of them being its huge young educated population. However, in the process, the older consumer segment has been ignored time and again. The country’s senior population, which is currently around 80 million is expected to increase to 137 million by 2021. Another study says that the age group of >60 years will increase from 62.3 to 112.9 million in India between 1996-2016. The dependency ratio will continue to decline (National Commission on Population). The 50-plus generation also defined as the silver generation is the wealthiest and fastest growing group of consumers in India. While everyone from economist and management consulting firms use the promise of a "Young India" as a compelling argument to pit India against an "Ageing China", the study by Harmony for Silvers Foundation says that the marketers might be missing the bigger picture. According to the study, this is a charmed generation which has a level of spending power unlikely to be matched by future generation. (seniorsworldchronicle.com ). It is with this background that the paper attempts to review the literature on the elderly consumer market on parameters like segmentation, product use and adoption and communication required to target the elderly consumers. The paper attempts to review and compare the results of West and India.